ARIMA Model for Forecasting COVID-19 Positivity Rate in Jakarta - Wardhani, Andreanne Intan Sulistyo; Ulya, Aulia Himmatul; Febrianti, Ranny; Suandi, Dani (Lembaga Penelitian dan Pengembangan Matematika dan Statistika Terapan Indonesia, PT Anugrah Teknologi Kecerdasan Buatan PT Anugrah Teknologi Kecerdasan Buatan, 2025)
COVID-19, a global pandemic since early 2020, has affected numerous countries worldwide, including Indonesia. The positivity rate serves as a crucial metric for gauging the extent of COVID-19 transmission in a specific region. The surge in COVID-19 cases in Jakarta has notably impacted various industries, particularly the healthcare sector. In this paper, ARIMA model is used to predict the number of daily COVID-19 cases in Jakarta. The optimal model for predicting the positivity rate over the next 10 days, from June 22, 2022, to July 1, 2022, is identified as ARIMA (1,1,3). The forecasting error is quantified by the MAE of 0.5625, MSE of 0.0161, RMSE of 0.1268, and MAPE of 0.68% all of which attest to its high accuracy. From a mathematical perspective, the outcomes of this study offer advantages by elucidating the utilization of the ARIMA technique for forecasting time series data, particularly in scenarios involving disease spread, necessitating meticulous management. Additionally, within the healthcare domain, these findings offer valuable insights into endeavors aimed at controlling infectious diseases, particularly COVID-19, should similar outbreaks occur in the future.